2021
DOI: 10.1186/s12879-021-06461-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased human respiratory syncytial virus activity during the COVID-19 pandemic in Japan: an ecological time-series analysis

Abstract: Background Non-pharmaceutical interventions (NPIs), such as sanitary measures and travel restrictions, aimed at controlling the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), may affect the transmission dynamics of human respiratory syncytial virus (HRSV). We aimed to quantify the contribution of the sales of hand hygiene products and the number of international and domestic airline passenger arrivals on HRSV epidemic in Japan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 78 publications
3
43
0
Order By: Relevance
“…Perhaps the biggest factor not considered in the model is mitigation strategies for reducing spread of SARS-CoV-2, such as wearing of masks and social distancing. These NPIs not only change the time course of the SARS-CoV-2 epidemic, but also help stem the spread of other respiratory viruses (Ngonghala et al, 2020 ) and are largely thought to be responsible for the lack of typical seasonal respiratory viruses in 2020 (Oh et al, 2021 ; Redlberger-Fritz et al, 2021 ; Wagatsuma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the biggest factor not considered in the model is mitigation strategies for reducing spread of SARS-CoV-2, such as wearing of masks and social distancing. These NPIs not only change the time course of the SARS-CoV-2 epidemic, but also help stem the spread of other respiratory viruses (Ngonghala et al, 2020 ) and are largely thought to be responsible for the lack of typical seasonal respiratory viruses in 2020 (Oh et al, 2021 ; Redlberger-Fritz et al, 2021 ; Wagatsuma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a fear that the combined effect of SARS-CoV-2 and illness due to these other respiratory viruses could lead to an excessive burden on the healthcare system (Kissler et al, 2020 ; Xu and Li, 2020 ), but in many parts of the world, the usual seasonal respiratory virus epidemics did not materialize (Casalegno et al, 2021 ; Eisen et al, 2021 ; Le Hingrat et al, 2021 ; Liu et al, 2021 ; Tempia et al, 2021 ; Williams et al, 2021 ). It's not clear if the suppression of other respiratory viruses is due to an interaction between SARS-CoV-2 and these other viruses or due to non-pharmaceutical interventions imposed to control the spread of SARS-CoV-2 (Oh et al, 2021 ; Redlberger-Fritz et al, 2021 ; Wagatsuma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Where there have been successful vaccination programs for COVID-19, social restrictions and travel restrictions have eased, and children and young adults are returning to schools and universities at a time when the influenza season usually commences [ 9 ]. Reduced exposure to more commonly circulating respiratory viruses reduces the levels of population immunity [ 9 , 11 , 12 ]. As an example, studies from the US, Europe, and Japan have shown that the social restrictions during the COVID-19 pandemic in mid-2020 reduced the levels of respiratory syncytial virus (RSV) infections in children [ 8 , 9 ].…”
mentioning
confidence: 99%
“…As an example, studies from the US, Europe, and Japan have shown that the social restrictions during the COVID-19 pandemic in mid-2020 reduced the levels of respiratory syncytial virus (RSV) infections in children [ 8 , 9 ]. However, RSV infection rates in children rose, and infection duration was prolonged when children returned to school in September 2020 [ 12 ].…”
mentioning
confidence: 99%
“…An extensive search for other pathogens identified respiratory syncytial virus (RSV) by PCR of a nasopharyngeal swab, confirming the diagnosis of RSV pneumonia, which rarely affects late phase stem cell transplant recipients [ 1 ]. Epidemic patterns of infectious viruses other than SARS‐CoV‐2 altered substantially in these 2 years, presumably due to the changes in social activities associated with SARS‐CoV‐2 pandemics [ 2 , 3 ]. For instance, RSV infection was highly suppressed in 2020 but had a resurgent outbreak in early summer 2021 [ 4 , 5 ].…”
mentioning
confidence: 99%